Dipeptidyl peptidase-4 inhibitor treatment could decrease Klebsiella pneumoniae pneumonia in patients with type 2 diabetes. Issue 8 (16th November 2020) - Chen, Hsin-Hung; Chen, Ching-Chu; Ho, Chun-Wei; Hsieh, Ming-Chia; Hsu, Sheng-Pang; Lin, Cheng-Li; Kao, Chia-Hung
ABSTRACT: Objectives: To investigate the effect of dipeptidyl peptidase-4 inhibitor (DPP4i) for Klebsiella pneumoniae (KP) pneumonia in patients with diabetes. Patients and methods: Patients newly diagnosed with type 2 diabetes from 2009 to 2012 were recruited for this population-based and observational study. Diabetes complications severity index (DCSI) score and defined daily dose (DDD) were used for analysis. The multivariable Cox proportional hazards models were used to estimate the risk of KP pneumonia by DPP4i use, with adjustments for propensity score. The Kaplan–Meier method with the log-rank test was used to estimate the risk of KP pneumonia for DPP4i users. Results: 34774 patients were included. The incidence rate of KP pneumonia in DDP4i users was 1.51 per 1000 person-years and that for the comparison was 2.25 per 1000 person-years. DDP4i users also had a significantly lower cumulative incidence of KP pneumonia (log-rank test p-value = 0.03). DDP4i users had a significantly lower risk of developing KP pneumonia compared with nonusers (adjusted HR = 0.67, 95% CI = 0.48–0.95). Conclusions: For public health issue with type2 diabetes and infection, DPP4i use decreased KP pneumonia. Male gender, patients with co-morbidities, patients with higher DSCI score and higher DDD of DPP4i were observed to decrease KP pneumonia infection in our analysis. The possible role of DPP4i causing immunological disturbances should be considered.